DIGITALIZATION OF INTERNATIONAL TOURISM: THE ROLE OF ARTIFICIAL INTELLIGENCE AND BIG DATA IN MANAGING TOURIST DEMAND - Umida Malikova (Modern American Journals, 2025)
This article examines sources of tourism demand data (search queries, social media, transactions, mobile positioning, and platform data), analytical and machine learning methods for demand forecasting and management, and institutional implementation conditions (data spaces, statistical standards, data governance, and privacy and bias risks). It is shown that the combination of multi-source data and AI improves the accuracy of short- and medium-term demand forecasts and enables a transition from reactive to proactive management, provided that high -quality validation, model transparency, and compliance with data protection requirements are ensured
Keywords: International tourism, digitalization, big data, artificial intelligence, demand forecasting, Google Trends, mobile data, social media, destination management, data governance.